The effects of electrode impedance on receiver sensitivity in body channel communication. (July 2016) - Bae, Joonsung; Yoo, Hoi-Jun
Abstract: The effects of the electrode interface on a receiver sensitivity in a body channel communication (BCC) are studied to clarify the characteristics of the electrode interface in the BCC, and revisit the noise and sensitivity analysis against the conventional method exploited in a radio frequency (RF) communication. First, the paper describes the noise characteristics in the electrode interface and examines the relationship between the noise and the contact impedance in the BCC frequency region. Then, we introduce a sensitivity analysis method dedicated to the BCC receiver by means of a receiver gain and an output noise spectral density. To verify the sensitivity analysis method, we implemented a direct conversion BCC receiver in 0.18 μm CMOS technology. By measuring the gain, output spectral density, and sensitivity of the receiver with respect to the various source impedance values, we found that the calculated value through the proposed analysis method agrees well with the theoretical value within 2.5 dB difference.